The Likelihood of Sustaining Nigerias Iron Ore Production in the Short-Run - Uche, Osemenam; B., Afeni Thomas (International Journal of Social and Administrative Sciences, 2019)
Given the attention of Nigerian policymakers to the sustenance of iron ore production in the national discourse on economic diversification. This write-up logically points out scenarios and reasons why the likelihood of sustaining this venture in the short-run could be very slim. The inference from the ideology of production possibility boundary is considered. In sum, the non-operation of Nigeria’s potential demand (identified as an indirect input, in this write up) for her iron ore concentrates by law, its deficient national income - which could hinder the procurement of sophisticated mining equipment to sustain iron ore mining and human capital limitation, are factors considered, to arrive at the aforementioned conclusion. Hence, the option of privatization is suggested, as a way of shifting the costs (Nigeria’s outrageous debt, which could lead to a debt crisis) accruable to absorbing these inadequacies, if the decision to sustain Nigeria’s iron ore production must be kept afloat.